2017
DOI: 10.5539/ijbm.v12n10p43
|View full text |Cite
|
Sign up to set email alerts
|

Conceptualizing Relational Resources as Critical Factor for IT Outsourcing Success

Abstract: The relational resources represent key assets for outsourcing success. Achieving full potential in the development and exploitation of relational resources in outsourcing can be understood as occurring in two closely intertwined phases: i. during the choice of the provider; ii. through the governance of the relation that develops over the execution of the contract. The current paper aims to provide conceptual insights into these two phases, as they apply to the particular area of companies' IT outsourcing. A f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(39 reference statements)
0
2
0
1
Order By: Relevance
“…Interestingly, this was different in research that found that “relationship interaction” (communication, cooperation, coordination, collaboration, conflict resolution and integration activities) has a greater impact on customer perceived value than “relationship quality” (loyalty and trust) in services outsourcing (Rhodes et al ., 2016). Nevertheless, this was refuted in recent research, which highlighted the paradigm shift from transaction-based outsourcing to partnership-based outsourcing, and relational resources have become an important factor for IT outsourcing success (Popoli, 2017).…”
Section: Theoretical Foundation Literature Review and Research Frameworkmentioning
confidence: 99%
“…Interestingly, this was different in research that found that “relationship interaction” (communication, cooperation, coordination, collaboration, conflict resolution and integration activities) has a greater impact on customer perceived value than “relationship quality” (loyalty and trust) in services outsourcing (Rhodes et al ., 2016). Nevertheless, this was refuted in recent research, which highlighted the paradigm shift from transaction-based outsourcing to partnership-based outsourcing, and relational resources have become an important factor for IT outsourcing success (Popoli, 2017).…”
Section: Theoretical Foundation Literature Review and Research Frameworkmentioning
confidence: 99%
“…In particular, this article examines the role of the 3PL's organizational capabilities in bringing logistics outsourcing success. Herein, logistics outsourcing success refers to the 3PL user's total satisfaction with the expected performance provided by a 3PL (Han et al, 2008; Popoli, 2007; Schwarz, 2014). More specifically, logistics outsourcing success reflects the overall benefits gained from logistics outsourcing (Yuan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A terceirização de TI tornou-se uma escolha estratégica das organizações em que as estruturas de TI são cada vez mais necessárias para tornar os processos de gestão não apenas mais eficientes e econômicos, mas também mais inovadores e flexíveis, capazes de condicionar eficácia e eficiência na execução dos processos [Popoli, 2017]. Na terceirização de força de trabalho, a organização contratada é responsável por fornecer força de trabalho (isto é, mão de obra) especializada com conhecimento, habilidades e experiências solicitadas e na quantidade desejada, conforme acordo previamente estabelecido com a organização contratante, que, por sua vez, é responsável pela gerência da força de trabalho disponibilizada pela contratada.…”
Section: Introductionunclassified